Literatur Yoga dan Ä€yurveda Sumber Komprehensif Ilmu Pengetahuan Kesehatan Holistik - Maheswari, Prasanthy Devi (Institut Hindu Dharma Negeri Denpasar, 2021)
The holy book of Hinduism, namely the Vedas, is a source of spiritual knowledge and scientific knowledge. Yoga and Ä€yurveda are part of Hindu science. Both are sources of holistic health science, where yoga is part of Sad Darsana and Ä€yurveda as a derivation of Caturveda, especially á¹šgveda. Yoga and Ä€yurveda will show their integrative relationship when viewed from the derivations or branches of the sacred Caturveda literature. If Caturveda is directly related to the ways of carrying out the union of the self with God using the ritual path, then Yoga Darsana is related to the discipline of self-unification using the path of physical, mental and spiritual health. In short, to attain union with God throughout life requires knowledge of yoga and Ä€yurveda, both theoretically and practically. One of the goals of health science is to provide a better life for humans. This health science provides knowledge about how to prevent and treat disease disorders. So the knowledge of yoga and Ä€yurveda is also learned to balance health conditions. If the science of Ä€yurveda can treat the human body, then the science of yoga can perfect this knowledge by being able to realize the balance of body, mind and spirit. That's moksartham Jagadhita ya ca iti dharma. If this information is conveyed communicatively by Hindus and readers of Hindu teachings, then misunderstanding of a knowledge can be avoided and then physical, mental and spiritual health will be achieved.